Wheat responses to sodium vary with potassium use efficiency of cultivars - Krishnasamy, Karthika; Bell, Richard; Ma, Qifu (Frontiers in Plant Science, 2014)
The role of varied sodium (Na) supply in K nutrition of wheat (Triticum aestivum L.) is not well understood especially among cultivars differing in K efficiency. We examined the response of K-efficient and K-inefficient Australian wheat cultivars to Na supply (low to high Na) under K-deficient and K-adequate conditions. In a pot experiment, wheat cvv Wyalkatchem, Cranbrook (K-efficient), and cvv Gutha, Gamenya (K-inefficient) were grown for 8 weeks in a sandy soil containing 40 or 100 mg K/kg in combination with nil, 25, 50, 100 or 200 mg Na/kg. High soil Na levels (100, 200 mg Na/kg) greatly reduced plant growth in all four cultivars especially at low soil K (40 mg K/kg). By contrast, low to moderate soil Na levels (25, 50 mg Na/kg) stimulated root dry weight at low K supply, particularly in K efficient cultivars compared with K-inefficient cultivars. At low K supply, low to moderate Na failed to increase shoot Na to a concentration where substitution of K would be feasible. However, low to moderate Na supply increased shoot K concentration and content in all four wheat cultivars, and it increased leaf photosynthesis and stomatal conductance to measured values similar to those under adequate K and nil Na conditions. The results showed that low to moderate Na stimulated K uptake by wheat particularly in K-efficient cultivars and through increased shoot K enhanced the photosynthesis. We conclude that increased photosynthesis supplied more assimilates that led to increased root growth and that greater root growth response of K-efficient cultivars is related to their greater K-utilisation efficiency. However, the process by which low to moderate Na increased shoot K content warrants further investigation.